2008
DOI: 10.1021/la802159t
|View full text |Cite
|
Sign up to set email alerts
|

Particle and Substrate Charge Effects on Colloidal Self-Assembly in a Sessile Drop

Abstract: By direct video monitoring of dynamic colloidal self-assembly during solvent evaporation in a sessile drop, we investigated the effect of surface charge on the ordering of colloidal spheres. The in situ observations revealed that the interaction between charged colloidal spheres and substrates affects the mobility of colloidal spheres during convective self-assembly, playing an important role in the colloidal crystal growth process. Both ordered and disordered growth was observed depending on different chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 47 publications
1
86
0
Order By: Relevance
“…1a and 1b can be attributed to the strong electrostatic attraction between oppositely charged PS particles. As shown in a recent study [37], the attractive hydrophobic interaction can limit the mobilities of hydrophobic PS spheres. This is driven by the reduction in surface energy on coagulation of hydrophobic spheres and is consistent with our observations.…”
Section: Resultsmentioning
confidence: 68%
“…1a and 1b can be attributed to the strong electrostatic attraction between oppositely charged PS particles. As shown in a recent study [37], the attractive hydrophobic interaction can limit the mobilities of hydrophobic PS spheres. This is driven by the reduction in surface energy on coagulation of hydrophobic spheres and is consistent with our observations.…”
Section: Resultsmentioning
confidence: 68%
“…The velocity of arrival below which the ordered phase formed is apparently set by the ratio of the time between successful arrivals of new particles to a position along the contact line to the time required for particles to rearrange by diffusion near the contact line . Consistent with this, Yan et al showed that by changing the charge of the particles relative to that of the substrate, or by addition of surfactant, the mobility of the particles at the contact line could be increased or decreased, thereby controlling whether ordered or disordered particle assemblies formed. For example, particles of charge opposite that of the surface were relatively immobile and formed a disordered deposit, while the opposite occurred for particles of the same charge as the substrate.…”
Section: Deposition Patternsmentioning
confidence: 94%
“…In our previous work, we have studied the influence of charge, including sphere's surface charge, substrate's surface charge, and surfactant's charge, on the ordering of self-assembly process [20]. It was found that significantly ordered self-assembly is only achieved when the colloidal spheres and the substrate possess the same sign of surface charge.…”
Section: Charge Effects On Self-assembly Of the 2d Colloidal Crystalsmentioning
confidence: 99%